We can substitute the value of "x" from the first equation into the second equation to get:
2(6y-3) + 7y = 13
Simplifying this:
12y - 6 + 7y = 13
Combining like terms:
19y = 19
Dividing both sides by 19:
y = 1
Now that we have the value of "y", we can substitute it back into the first equation to solve for "x":
x = 6(1) - 3 = 3
Therefore, the solution to the system of equations is (x,y) = (3,1).
Solve the system of equations.
x=6y−3
2x+7y=13(1 point)
2 answers
1) 3,1
2) -2,2
3) 4,-3
4) -2,-6
5) 0
2) -2,2
3) 4,-3
4) -2,-6
5) 0